Climatic water balance and length of growing period for efficient crop planning under different agrotopo-climate in Ranchi, Jharkhand - KUMARI, PRAGYAN; BALMUCHU, SUNNY ASHISH; TIRKEY, DEEPAK A.; WADOOD, A. (Journal of Soil and Water Conservation, 2020)
The study was carried out to estimate the water balance and length of growing period under four different types of topographical situation for efficient crop planning in Ranchi region. Length of growing season analysis reveals that it was 154 and 182 days for Upland and Upper medium land (Don III) while 203 days for both lower medium land (Don II) and Low land (Don I), respectively. In view of the different water related conditions in different land situations, crop diversification would be practicable in uplands as well as in medium lands. Direct seeded rice in upland (Tand) and direct as well as transplanted rice in medium lands may be replaced, to some extent, with less water requiring crops like maize, oilseeds and pulses. However, in typical lowland (Don I) farmers do not have much option for crop diversification or replacement except to go for transplanted paddy. Local climate analysis indicated that it varies from semi arid for Tand areas to moist sub humid condition for low-lying areas.